Perkembangan Ekosistem Ekonomi Digital di Indonesia : Sebuah Kajian Literatur - Diky Budiman; Sri Iswati; Mey Krisselni Sitompul (JUMINTAL: Jurnal Manajemen Informatika dan Bisnis Digital, 2025)
This research aims to examine in depth the concepts, characteristics, and challenges in the development of the digital economy ecosystem through a literature study approach. The digital economic ecosystem is a complex and interconnected network that includes businesses, consumers, technology service providers, and governments, all operating within a rapidly evolving digital environment. This study specifically focuses on four key components: e-commerce, on-demand services, online travel agents, and financial technology (fintech), which represent the most dynamic sectors in the current digital economy. By analyzing a range of academic literature published within the last five years, this research highlights that while digital technology advancement has unlocked significant opportunities for inclusive and sustainable economic growth, it also introduces challenges such as cybersecurity risks, regulatory uncertainties, and widening digital inequality. The findings are expected to contribute to a deeper and more holistic understanding of the formation and sustainability of digital economic ecosystems, particularly in the context of developing economies like Indonesia, where digital transformation is progressing rapidly across various sectors.